Pengaruh Word Of Mouth, Harga Dan Cita RasaTerhadap Keputusan Pembelian Sambal Cumi Dan Udang - Novri Wardana; Adcharina Pratiwi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of Word of Mouth (WOM), price and taste on purchasing decisions for squid and shrimp chili sauce, especially for Sambel Domble customers. The research method used was a survey by distributing questionnaires to 100 respondents who were Sambel Domble customers. The collected data was tested using instrument tests using validity and reliability tests. The classical assumption test uses tests: multicollinearity, heteroscedasticity, autocorrelation and normality. Data analysis techniques use multiple linear regression tests, t tests, F tests and R² tests.The results of the research show that Word of Mouth (WOM), price and taste together have a significant influence on purchasing decisions for squid and shrimp chili sauce for Sambel Domble customers.